The Influence of the Role Playing Method on Improving First Aid Skills in PMR Extracurricular Activities at SMP Negeri 7 Padang - Nurul Fitri Febriyanti; Jamaris Jamaris (Universitas Negeri Padang, 2023)
This research is motivated by the low skills and knowledge of first aid in PMR extracurricular which is thought to be caused by the media used by the trainer in the training process. Therefore, it is necessary to renew the training method using the role playing method. This study aims to see the effect of using the role playing method in improving the skills of helping participants in PMR extracurricular activities at SMP Negeri 7 Padang. This type of research is quantitative with an experimental approach to pre-experimental design using a one group pretest-posttest design. The population in this study were all participants in PMR extracurricular activities. Sampling was done by random sampling. Data collection techniques using pretest and posttest. The data collection tool is a skill test in the form of an assessment guide and a knowledge test in the form of test questions. Meanwhile, the data analysis technique used the correlation sample t-test formula. The results showed that there was a significant effect between the use of the role playing method in improving first aid skills with the value of th < to -7,226 < 2,001 on the skill test and th < to which was -7,998 < 2,001 on the knowledge test.Keywords: Role playing method, first aid skills, PMR extracurricular.